Fluctuations in food and fluid intake during a 24-h World Championship: analysis of the deviation from nutritional programs - Keyne Charlot; Chloé Lavoué; Julien Siracusa; Emeric Chalchat; Pierre Hertert; Cyprien Bourrilhon (Taylor & Francis Group, 2022)
Background A food and fluid intake program is essential for ultraendurance athletes to maximize performance and avoid possible gastrointestinal symptoms (GIS). However, the ability to follow such a program during a race has been under-assessed. We thus investigated the fluctuations of food and fluid intake during the 24-h run World Championship of 12 elite athletes (6 men and 6 women; age: 46 ± 7 years, height: 170 ± 9 cm, weight: 61.1 ± 9.6 kg, total distance run: 193-272 km) and assessed their ability to follow their nutritional program. Methods Real-time overall intake (fluids, energy, and macronutrients) was recorded and compared to that of their program. The temporal difference in absolute values and the degree of divergence from their program were assessed, divided into four 6-h periods. GIS were recorded during the race. A questionnaire identifying the details of their nutritional program and the self-assessed causes of their inability to follow it was completed by the participants the day after the race. Results Water, total fluid, carbohydrates (CHO), and energy intake decreased during the last quarter of the 24-h ultramarathon relative to the first half (p = 0.024, 0.022, 0.009, and 0.042). However, the differences were no longer significant after these values were normalized by the number of passages in front of the supply tent. The participants progressively failed to follow their nutritional program, with the intake of their planned items dropping to approximately 50% during the last quarter. However, this was adequately compensated by increases in unplanned foods allowing them to match their expected targets. GIS, lack of appeal of the planned items, and attractivity of unplanned items were the main explanations given for their deviation from the program (64, 27, and 27%, respectively). Conclusion Despite evident difficulty in following their nutritional programs (mostly attributed to GIS), elite ultraendurance runners managed to maintain high rates of fluid and food intake during a 24-h ultramarathon and therefore still met their planned elevated nutritional objectives. Abbreviations: CHO: carbohydrates, GIS: gastrointestinal symptoms